A Hydroxamic Acid Anchoring Group for Durable Dye‐Sensitized Solar Cells Incorporating a Cobalt Redox Shuttle. Issue 17 (16th August 2017) - Higashino, Tomohiro; Kurumisawa, Yuma; Cai, Ning; Fujimori, Yamato; Tsuji, Yukihiro; Nimura, Shimpei; Packwood, Daniel M.; Park, Jaehong; Imahori, Hiroshi
Abstract: A hydroxamic acid group has been employed for the first time as an anchoring group for cobalt‐based dye‐sensitized solar cells (DSSCs). The porphyrin dyeYD2‐ o ‐C8HA including a hydroxamic acid anchoring group exhibited a power conversion efficiency ( η ) of 6.4 %, which is close to that ofYD2‐ o ‐C8, a representative porphyrin dye incorporating a conventional carboxylic acid. More importantly, YD2‐ o ‐C8HA was found to be superior toYD2‐ o ‐C8 in terms of both binding ability to TiO2 and durability of cobalt‐based DSSCs. Notably, YD2‐ o ‐C8HA photocells revealed a higher η ‐value (4.1 %) thanYD2‐ o ‐C8  (2.8 %) after 500 h illumination. These results suggest that the hydroxamic acid can be used for DSSCs with other transition‐metal‐based redox shuttle to ensure high cell durability as well as excellent photovoltaic performance. Abstract : HA‐py DSSCs : A hydroxamic acid (HA) group has been employed for the first time as an anchoring group for a cobalt‐porphyrin‐based dye‐sensitized solar cell (DSSC). HA could be used with other organic‐based dyes for DSSCs with various transition‐metal‐based redox shuttles to balance high cell durability and good performance.